ASSESSMENT OF COGNITIVE STATUS IN ELDERLY PERSONS IN THE COMMUNITY - Zivanovic, Srdjan (PONS - medicinski časopis, 2023)
Introduction. Aging is characterized by the loss of abilities in the psychological and physical sense. Detailed assessment of cognitive status may enable early identification of high-risk patients who are candidates for dementia. The aim of this research was to examine the cognitive status of elderly people over 65 years of age living in the community and potential risk factors that contribute to the onset of dementia.Material and methods. The research was designed according to the principle of a cross-sectional study. The research used a general questionnaire, subjective and objective assessment of respondents, Mini Kog assessment. The χ2 square test was used for statistical tests, and Pearson's correlation analysis was used for association analysis. The usual value of p
Keywords: age; instruments; cognitive assessment; dementia; elderly people